Psychological Capital Differs Among Rural Left-Behind Children and Is Associated With Emotional and Behavioral Problems - Zhu, Cuiying; Yin, Xiaolan; Li, Zhihua; Zhou, Lujun (Frontiers in Psychology, 2021)
This study aims to explore, through latent profile analysis, rural left-behind children’s psychological capital and its relationship with emotional and behavioral indicators. In this study, 677 rural-based left-behind children (average age 11.7 ± 1.58 years) in Hunan Province, China, were recruited and assessed using the Rural Left-behind Children’s Psychological Capital Questionnaire and the Children’s Strengths and Difficulties Questionnaire. We found that psychological capital was divided into three latent profiles: high (43.7% of the sample), medium (45.9%), and low (10.3%). Compared to the other two types, the children with low psychological capital returned higher scores for emotional symptoms, conduct disorder, hyperactivity and impulsivity, and peer-interaction problems, but lower prosocial behavior scores. Meanwhile, examination of the effects of gender and grade found that most of the elementary school students had high psychological capital, and that there was no significant difference among the groups in regard to gender. In summary, distinct differences in psychological capital were found among left-behind children, and the latent profiles were determined to be related to grade, emotional symptoms, hyperactivity and impulsivity, and prosocial behavior. There was also a significant difference in emotional and behavioral indicators across the different latent profiles.